Ekologi dan Kerusakan Lingkungan dalam Persepektif Al-Qur’an - L. Sholehuddin (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2021)
Ecosystem is an overall unified arrangement of elements of the environment that influence each other in creating balance, order and sustainability. The discourse on environmental conservation has become an actual issue in the midst of the threat of a global crisis as a consequence of disasters, climate change, global warming, erratic seasonal changes, decreased quality of life and the threat of destruction of the earth. This condition triggers the anxiety and worry of mankind about the extinction of the earth. This study will answer how the Koran talks about the environment and its impact on human life. The design of this research is a qualitative type of literature. The data collection technique is the documentation of collecting environmental damage verses. The analysis uses a comparative interpretive, namely examining verses on environmental damage, comparing them, then concluding them through inductive thinking. The results of the study prove that environmental damage is caused by polytheists, hypocrites, greedy and selfish people. Solutions for strengthening monotheism, awareness of environmental law, and moral natural resource management.